2017
DOI: 10.1016/j.virol.2017.05.018
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between HIV-1 Nef and adaptor protein-2 reduces Nef-mediated CD4+ T cell apoptosis

Abstract: Acquired Immune Deficiency Syndrome is characterized by a decline in CD4 T cells. Here, we elucidated the mechanism underlying apoptosis in Human Immunodeficiency Virus-1 (HIV-1) infection by examining host apoptotic pathways hijacked by the HIV-1 Nef protein in the CD4 T-cell line Sup-T1. Using a panel of Nef mutants unable to bind specific host proteins we uncovered that Nef generates pro- and anti-apoptotic signals. Apoptosis increased upon mutating the motifs involved in the interaction of Nef:AP-1 (Nef or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Nef also binds and activates the serine/threonine kinase p21 activated kinase 2 (PAK2), which induces T cell activation [ 57 ]. Nef thus alters the activation status of cells, perhaps inducing the correct balance between activating and inhibitory signaling, thereby enabling optimal viral replication without inducing anergy or activation induced cell death [ 75 ]. However, when compared to Nef, little is known regarding how Vpu alters T cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Nef also binds and activates the serine/threonine kinase p21 activated kinase 2 (PAK2), which induces T cell activation [ 57 ]. Nef thus alters the activation status of cells, perhaps inducing the correct balance between activating and inhibitory signaling, thereby enabling optimal viral replication without inducing anergy or activation induced cell death [ 75 ]. However, when compared to Nef, little is known regarding how Vpu alters T cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction between adipocyte and immune cells The consequences of a lipid-rich environment Mazzon and Mercer, 2014 Oxidative stress Malmberg et al, 2001;Ivanov et al, 2016 Hypoxia in adipose tissue Tao et al, 2015 Insulin sensitivity Tsai et al, 2018 Viral and pharmacological parameters HIV viral proteins Boya et al, 2004;Debaisieux et al, 2012;Clark et al, 2017;Jacob et al, 2017 Adipose tissue remodeling and fibrosis Sun et al, 2013;Vila et al, 2014;Marcelin et al, 2017 Antiretroviral diffusion (ARV) Dupin et al, 2002; impact on the persistence of HIV-infected CD4 T cells, and might also interfere with the effective differentiation of memory cells. Indeed, CD4 T cell help is a crucial factor in the differentiation and maintenance of CD8 T cells.…”
Section: Limited Efficiency Of Ag Presenting Cellsmentioning
confidence: 99%
“…It has been shown that the HIV proteins Tat, Nef, gp120, and Vpr can modulate immune cells, notably by inducing the apoptosis of non-infected CD4 T cells as a bystander effect (Boya et al, 2004). Nef binds to CXCR4 and modulates T cell activation (Jacob et al, 2017), and so may also be involved in HIV persistence. Tat induces apoptosis in non-infected CD8 and CD4 T cells, and alters the metabolic, morphologic, and biochemical properties of CD4 T cells (Debaisieux et al, 2012;Faller et al, 2014;Clark et al, 2017).…”
Section: Hiv Viral Proteins Affecting Immune Cellsmentioning
confidence: 99%
“…The AP-2 complex is involved in a variety of biological processes. 10,29 However, no studies have been conducted on the roles of AccAP2m in response to adverse stress conditions in A. cerana cerana. Adult worker bees are responsible for pollen collection, pollination, and other works; because of high levels of contact with the external environment, these bees are easily affected by the F I G U R E 3 AccAP2m transcription expression level under environmental stress factors.…”
Section: Discussionmentioning
confidence: 99%